2016
DOI: 10.5312/wjo.v7.i9.604
|View full text |Cite
|
Sign up to set email alerts
|

Arterial complications, venous thromboembolism and deep venous thrombosis prophylaxis after anterior cruciate ligament reconstruction: A systematic review

Abstract: AIMTo summarize the current knowledge on vascular complications and deep venous thrombosis (DVT) prophylaxis after anterior cruciate ligament (ACL) reconstruction.METHODSA systematic review was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses statement. MEDLINE, EMBASE, Cochrane, Web of Science, CINAHL, PubMed publisher, and Google scholar medical literature databases were searched up to November 10, 2015. Any arthroscopic surgical method of primary or revision intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 61 publications
0
56
1
Order By: Relevance
“…VTE is a significant perioperative complication occurring after many orthopaedic procedures, especially surgeries involving the knee. 1 , 2 , 5 , 8 , 13 There is currently no standard recommendation for chemical prophylaxis after ACL reconstruction. This study’s findings show that 50% of sports medicine fellowship–trained orthopaedic surgeons in the United States routinely use chemical prophylaxis for perioperative thrombotic risk after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VTE is a significant perioperative complication occurring after many orthopaedic procedures, especially surgeries involving the knee. 1 , 2 , 5 , 8 , 13 There is currently no standard recommendation for chemical prophylaxis after ACL reconstruction. This study’s findings show that 50% of sports medicine fellowship–trained orthopaedic surgeons in the United States routinely use chemical prophylaxis for perioperative thrombotic risk after ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) is a significant perioperative risk with many common orthopaedic procedures. 1 , 5 , 8 , 13 ACL reconstruction carries a risk of developing symptomatic and asymptomatic DVT. A previous systematic review reported the risks of developing asymptomatic DVT, symptomatic DVT, and pulmonary embolism (PE) after ACL reconstruction were 8.4%, 2.3%, and 0.2%, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudoaneurysms differ from true aneurysms in that they do not contain all the layers of an artery. 1 A pseudoaneurysm evolves into a haematoma if blood passes through the adventitia and collects in the surrounding tissue external to the three vessel layers. Damage occurs due to partial division and erosion of the pulsating arterial wall, often by the projection of metallic screws or hardware.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular complications after ACL reconstructions are rare but can cause serious morbidity and potential mortality [ 4 ]. Vascular complications may occur after various methods of reconstruction and fixation [ 5 ]. Since 2013, we have switched to the all-inside ACL reconstruction technique (Arthrex, München).…”
Section: Introductionmentioning
confidence: 99%